2020
DOI: 10.1177/2058738420954594
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study on the anti-apoptotic mechanism of Astragaloside IV on radiation-induced brain cells

Abstract: With multiple targets and low cytotoxicity, natural medicines can be used as potential neuroprotective agents. The increase in oxidative stress levels and inflammatory responses in the brain caused by radiation affects cognitive function and neuronal structure, and ultimately leads to abnormal changes in neurogenesis, differentiation, and apoptosis. Astragaloside Ⅳ (AS-Ⅳ), one of the main active constituents of astragalus, is known for its antioxidant, antihypertensive, antidiabetic, anti-infarction, anti-infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The anti-apoptotic activity of AS-IV has been described previously. Liu et al (2020) reported that AS-IV prevented radiation-induced apoptosis in brain cells by suppressing the expression of pro-apoptotic proteins. In another study, Liu et al (2017) demonstrated that AS-IV protected against IL-1β-induced chondrocyte apoptosis by upregulating autophagy activity in chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-apoptotic activity of AS-IV has been described previously. Liu et al (2020) reported that AS-IV prevented radiation-induced apoptosis in brain cells by suppressing the expression of pro-apoptotic proteins. In another study, Liu et al (2017) demonstrated that AS-IV protected against IL-1β-induced chondrocyte apoptosis by upregulating autophagy activity in chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…After the injury, neural stem cells are attracted to some factors and cross the blood-brain barrier to accumulate at high levels at the injury site; hence, these cells can be targeted for treating neurological diseases such as PD and Frozen disease. AS-IV counters the radiation-induced senescence of brain cells by regulating the p53-p21 and p16-RB senescence-regulated signaling pathways and JNK-p38 phosphorylation [ 38 , 39 ]. Furthermore, the combination of AS-IV and ginsenoside Rg1 augments the protective effects against cerebral ischemic injury via antiapoptotic and anti-inflammatory effects.…”
Section: Neuroprotective Effectsmentioning
confidence: 99%
“…Many homologous ingredients of medicine and food, such as polysaccharides, flavonoids, saponins, peptides, alkaloids, and vitamins, have been found to have antiradiation activities 5–7 . As a medicinal and food homologous plant, Acanthopanax senticosus ( AS ) is widely grown in China, and is also often used as a wild vegetable.…”
Section: Introductionmentioning
confidence: 99%
“…Many homologous ingredients of medicine and food, such as polysaccharides, flavonoids, saponins, peptides, alkaloids, and vitamins, have been found to have antiradiation activities. 5 , 6 , 7 As a medicinal and food homologous plant, Acanthopanax senticosus ( AS ) is widely grown in China, and is also often used as a wild vegetable. Previous studies have confirmed the ability of AS to improve learning and memory, increase the number of neurons, prevent brain damage, and have good therapeutic effects on central degenerative diseases and cerebrovascular diseases.…”
Section: Introductionmentioning
confidence: 99%